(untitled) (Scientific journal of the Fergana State University, 2024)
This paper presents a comprehensive analysis of J.D. Salinger’s literary contributions, focusing on themes, character development, and narrative techniques. By examining his major works, including "The Catcher in the Rye," "Nine Stories," and "Franny and Zooey," this study employs a mixed-methods approach to understand Salinger’s influence on contemporary literature. Qualitative content analysis highlights recurring themes such as alienation, innocence, and existential angst, while quantitative analysis evaluates the frequency of thematic elements and character archetypes across his works. The results indicate that Salinger’s portrayal of adolescent turmoil and societal critique remains relevant, influencing modern storytelling. This study underscores the enduring legacy of Salinger’s oeuvre in the literary canon and provides a nuanced understanding of his stylistic and thematic innovations.